Students' Problem Solving Strategies in Solving Equation and Linear Inequality Problems of One Variable - Nadhifah Kansah Hanif; Tina Yunarti; Wayan Rumite; Niki Pujarwati (Lembaran Ilmu Kependidikan, 2026)
Students’ ability to solve mathematical problems not only reflected their mastery of concepts, but also illustrated their way of thinking and the strategies they used when dealing with cognitive challenges. This study aimed to identify and describe the problem-solving strategies used in solving linear equations and inequalities with one variable. The research employed a qualitative approach with a single instrumental case study design and an evaluative method. Three students were selected from 29 potential participants. Data were collected through task sheets on linear equations and inequalities and semi-structured interviews. Data analysis was carried out in three stages: data condensation, data display, and conclusion drawing. The study revealed three strategies used by students in solving problems, namely logical reasoning, data organization, and trial and error. Each strategy operated under different principles when addressing the problems.